Role of soluble ST2 in short-term prediction of acute heart failure in acute ST-elevation myocardial infarction - O. S. Donirova; K. V. Protasov; B. A. Donirov; E. V. Batunova (Российский кардиологический журнал, 2021)
Aim. To investigate the relationship of soluble ST2 (sST2) to acute heart failure (AHF) and compare the predictive value of sST2 and brain natriuretic peptide in patients with ST-elevation myocardial infarction (STEMI).Material and methods. In 136 STEMI patients, the serum sST2 concentration was determined during the first 24 hours of hospitalization. We assessed levels of sST2, N-terminal pro-brain natriuretic peptide (NT-proBNP), incidence of Killip class II-IV AHF during hospitalization, myocardial necrosis biomarkers, parameters of complete blood count and biochemical blood tests, the incidence of cardiovascular diseases and risk factors. The predictive value of sST2 for AHF development was assessed using logistic regression. ROC analysis was performed. The areas under the ROC curve were compared for sST2 and NT-proBNP. The cut-off sST2 value was determined for predicting AHF.Results. The mean sST2 level was 43,4 (33,6-73,9) ng/ml. During the followup period, AHF was diagnosed in 54 people (39,7%). The prevalence of AHF in the 1st, 2nd and 3rd tertiles of sST2 was 15,6%, 33,3% and 69,7%, respectively. The NT-proBNP levels were 319 (128-1072) pg/ml, 430 (147-1140) pg/ml and 1317 (533-2386) pg/ml. The predictive value of 3rd sST2 tertile was retained adjusted for age, sex, NT-proBNP, troponin T, creatine phosphokinase-MB, high-sensitivity C-reactive protein, hemoglobin, blood glucose, left ventricular ejection fraction. The areas under the ROC curves for sST2 and NT-proBNP were comparable (0,828 and 0,733, respectively; p=0,056). The cut-off sST2 value was 64 ng/ml, above which the odds ratio of AHF was 11,1 (95% confidence interval, 4,7-26,1.Conclusion. An increase in blood sST2 is associated with an increase in AHF (Killip II-IV) prevalence in hospitalized patients with acute STEMI. Soluble ST2 has an independent predictive value for AHF in STEMI, comparable in strength and predictive model quality to NT-proBNP. The cut-off sST2 value for AHF (>64 ng/ ml) was calculated, which provides an optimal balance of sensitivity, specificity and accuracy of the prognostic model. These data support the potential value of sST2 as a biomarker of AHF in STEMI.